(untitled) (Central Asian Journal of Medical Sciences, 2023)
Objective: In the present study, we compared LASIK flap thickness predictability created by a FS laser versus a Moria microkeratome in Mongolian patients. Methods: A total of ninety-six candidates for the LASIK procedure were stratified into two groups: FS laser-assisted and MK flap creation. Flap thickness was determined at five points. The side-cut angle was measured in three directions at the margin interface. LASIK flap assessment was performed one month postoperatively by Spectralis anterior segment optical coherence tomography. Results: Ninety-five participants (190 eyes) were recruited; 190 eyes were stratified to the FS group and 78 eyes to the MK group. The FS group had relatively even flap configurations, and the MK group had meniscus-shaped flaps. Regarding CR-sphere and cylinder, there was significant difference between 2 groups. The mean cylinder was -1.216 ± 0.924 in FS group while it was -0.730 ± 0.738 in MK group. Similarly, the mean sphere was -3.635 ± 2.031 in FS-LASIK group and -2.984 ± 1.502 in MK-LASIK group. The side-cut architecture varied among the two groups. OCT-C and OCT1Temporal values were significantly different between two groups. Conclusion: Improving the predictability of LASIK flap thickness and morphology is significantly important.